Structure-based synthesis – from natural products to drug prototypes - Stephen Hanessian (ՀՀ ԳԱԱ հրատ.)
X-Ray crystallographic data available from complexes of natural and synthetic molecules with the enzyme thrombin has led to the design and synthesis of truncated and hybrid molecules exhibiting excellent inhibition in vitro.
Keywords: Քիմիա